Association Between Lysine Reduction Therapies and Cognitive Outcomes in Patients With Pyridoxine-Dependent Epilepsy. (6th December 2022) - Coughlin, Curtis R.; Tseng, Laura A.; Bok, Levinus A.; Hartmann, Hans; Footitt, Emma; Striano, Pasquale; Tabarki, Brahim M.; Lunsing, Roelineke J.; Stockler-Ipsiroglu, Sylvia; Gordon, Shanlea; Van Hove, Johan L.K.; Abdenur, Jose E.; et al.
Abstract : Background and Objectives: Pyridoxine-dependent epilepsy (PDE-ALDH7A1) is a developmental epileptic encephalopathy characterized by seizure improvement after pyridoxine supplementation. Adjunct lysine reduction therapies (LRTs) reduce the accumulation of putative neurotoxic metabolites with the goal to improve developmental outcomes. Our objective was to examine the association between treatment with LRTs and cognitive outcomes. Methods: Participants were recruited from within the International Registry for Patients with Pyridoxine-Dependent Epilepsy from August 2014 through March 2021. The primary outcome was standardized developmental test scores associated with overall cognitive ability. The relationship between test scores and treatment was analyzed with multivariable linear regression using a mixed-effects model. A priori, we hypothesized that treatment in early infancy with pyridoxine and LRTs would result in a normal developmental outcome. A subanalysis was performed to evaluate the association between cognitive outcome and LRTs initiated in the first 6 months of life. Results: A total of 112 test scores from 60 participants were available. On average, treatment with pyridoxine and LRTs was associated with a nonsignificant increase of 6.9 points (95% CI −2.7 to 16.5) on developmental testing compared with treatment with pyridoxine alone. For the subanalysis, a total of 14 developmental testing scores were available from 8 participants. On average, treatment with pyridoxine and LRTs in the first 6 months of life was associated with a significant increase of 21.9 points (95% CI 1.7–42.0) on developmental testing. Discussion: Pyridoxine and LRTs at any age was associated with mild improvement in developmental testing, and treatment in early infancy was associated with a clinically significant increase in developmental test scores. These results provide insight into the mechanism of intellectual and developmental disability in PDE-ALDH7A1 and emphasize the importance of treatment in early infancy with both pyridoxine and LRTs. Classification of Evidence: This study provides Class IV evidence that in PDE-ALDH7A1, pyridoxine and LRTs compared with pyridoxine alone is not significantly associated with overall higher developmental testing scores, but treatment in the first 6 months of life is associated with significantly higher developmental testing scores.